2017
DOI: 10.1042/bsr20170710
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of microRNA-374 on proliferation, migration, invasion, and apoptosis of human SCC cells by targeting Gadd45a through P53 signaling pathway

Abstract: Correspondence: or Bao-Guo Liu (liubaoguolbg@yeah.net) The present study investigated the effects of microRNA-374 (miR-374) on human squamous cell carcinoma (SCC) cell proliferation, migration, invasion, and apoptosis through P53 signaling pathway by targeting growth arrest and DNA-damage-inducible protein 45 α (Gadd45a). Skin samples were collected from patients with skin SCC and normal skin samples. Expression of miR-374, Gadd45a, P53, P73, P16, c-myc, bcl-2, Bax, caspase-3, and caspase-9 were detected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Moreover, the repression of DNMT1 by CH-5 could be reduced by overexpression of Sp1. Gadd45a gene is a DNA damage-inducible gene that participates in p53-dependent apoptosis [ 47 ] and is upregulated by activated p53 [ 48 ]. The expression of Gadd45a could be induced in p53 wild-type HCT116 cells treated with CH-5, but not in p53-null HCT116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the repression of DNMT1 by CH-5 could be reduced by overexpression of Sp1. Gadd45a gene is a DNA damage-inducible gene that participates in p53-dependent apoptosis [ 47 ] and is upregulated by activated p53 [ 48 ]. The expression of Gadd45a could be induced in p53 wild-type HCT116 cells treated with CH-5, but not in p53-null HCT116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding skin cancer, Ning et al revealed that miR‐374c expression was down‐regulated by next‐generation sequencing and RT‐qPCR assay in Merkel cell carcinoma and other cutaneous tumors compared with normal skin. In 2017, Li et al observed that miR‐374a expression was decreased in skin tissues of human squamous cell carcinoma compared to the normal skin tissue. Meanwhile, they verified through transfection of miR‐374 mimics into A431 and SCL‐1 cells, that miR‐374a down‐regulated the P53 signaling pathway to induce cell apoptosis and inhibit proliferation, migration and invasion by targeting its downstream protein, Gadd45a.…”
Section: The Role Of Mir‐374 In Tumorigenesismentioning
confidence: 99%
“…43 Li et al reported that microRNA-374 affected the proliferation, migration, invasion and apoptosis of cSCC cells by targeting Gadd45a through the p53 signaling pathway. 44 However, the mechanism of wogonoside on cSCC has not been clarified. We found that phosphorylation of AKT and βcatenin was significantly reduced by wogonoside treatment, while it had little effect on STAT3 and p65.…”
Section: Discussionmentioning
confidence: 99%